2018
DOI: 10.1089/tmj.2017.0112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telehealth Interventions on Quality of Life of Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: The results indicate that telehealth interventions are as effective at improving QOL scores in patients undergoing cancer treatment as in-person UC. Further studies should be undertaken on different modalities of telehealth to determine its appropriate and effective use in interventions to improve the QOL for cancer patients undergoing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 37 publications
4
100
0
Order By: Relevance
“…The overall grade of satisfaction with VC amongst surgeons was higher (9, IQR 9-10) than for the F2F-consult (8,. In both groups, surgeons felt they had discussed everything that was necessary in all of the included cases.…”
Section: Provider Satisfaction With the Consultmentioning
confidence: 89%
See 1 more Smart Citation
“…The overall grade of satisfaction with VC amongst surgeons was higher (9, IQR 9-10) than for the F2F-consult (8,. In both groups, surgeons felt they had discussed everything that was necessary in all of the included cases.…”
Section: Provider Satisfaction With the Consultmentioning
confidence: 89%
“…The use of VC in ambulatory patients undergoing treatment for, or recovering from, colorectal cancer has not been investigated to date according to literature. In patients with colorectal cancer there are no studies reporting on the attitude, use of and/or satisfaction with VC as an alternative for face-to-face (F2F) consultation [8]. Specific concerns may arise on the use of VC for patients with malignant disease, when complex information needs to be shared and when physical aftercare is multidisciplinary and compound [9].…”
mentioning
confidence: 99%
“…Our study found similar results to a recent meta-analysis of cancer patients in treatment that found the QOL assessment used made a significant difference in the mean effect of those in the telehealth intervention compared with those in UC. 34 Our study showed that the mean effect for the FACT assessment study group was significant, whereas using the EORTC-QLQ-C30 assessment did not yield a statistically significant effect on cancer survivors QOL. 34 The assessments were used with a variety of technology types and forms of cancer.…”
Section: Discussionmentioning
confidence: 50%
“…34 Our study showed that the mean effect for the FACT assessment study group was significant, whereas using the EORTC-QLQ-C30 assessment did not yield a statistically significant effect on cancer survivors QOL. 34 The assessments were used with a variety of technology types and forms of cancer. This is interesting when attempting to compare studies using slightly different assessment techniques and if they are comparable given differences in measurements.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation